Effect of Holder pasteurization on macronutrients and energy content of pooled donor human milk - Pasqua Anna Quitadamo; Leonilde Sorrentino; Giuseppina Palumbo; Liliana Cianti; Massimiliano Copetti; Maria Assunta Gentile; Pierpaolo Cristalli; Massimo Pettoello Mantovani (Hygeia Press di Corridori Marinella, 2021)
Background: Donor human milk (DHM) is the best option for preterm nutrition when mother's milk is unavailable. For its proven benefits on the life and health of premature babies, DHM should be part of the essential newborn care. The fortification of human milk is necessary to ensure adequate growth and consequent good neurodevelopment. Holder pasteurization is routinely practiced in human milk banks (HMBs) to ensure safety of DHM but can impact the macronutrient content. The aim of this study was to explore the effect of Holder pasteurization on fat, protein, lactose and energy content of DHM and compare our data with the literature. Methods: Protein, lactose, fats and energy of 100 DHM pools from 87 women were analyzed before and after Holder pasteurization using Miris HMA™ (Human Milk Analyzer, Miris AB, Uppsala, Sweden), with the infrared spectroscopic method. The mean macronutrient contents before and after Holder pasteurization were compared using paired t-tests, and the variations in the concentration of the components were calculated as Delta%. The data obtained were compared to other studies with the same purpose. Results: We observed a reduction in fat (3.12 ± 1.64 vs 2.55 ± 0.85, with Delta% -14.9 ± 13.0 and p-value < 0.0001), T protein (1.05 ± 0.26 vs 0.89 ± 0.20, with Delta% -8.9 ± 63.0 and p-value < 0.0001), energy content (61.38 ± 18.66 vs 55.00 ± 8.27, with Delta% -8.1 ± 9.4 and p-value 0.0001), while no significant changes were observed for lactose content (6.35 ± 0.80 vs 6.43 ± 0.58, with Delta% 6.5 ± 56.7 and p-value 0.3735). Data in the literature on the effect of Holder pasteurization on DHM macronutrients are variable, and the only constant element is the non-variation of the carbohydrate content. Conclusion: Holder pasteurization decreased protein, fat and energy content of DHM. The lactose content has not been affected after the Holder pasteurization. After having assessed a remarkable variation in the macronutrient content in comparison with other studies, the adjustable fortification, especially if based on the composition data, might be more accurate. In addition, despite the fact that Holder pasteurization is actually the method recommended by the international HMB guidelines, as it provides a compromise between microbiological safety and nutritional/biological quality of DHM, studies on alternative methods capable of treating DHM preserving the milk's components are desirable.